GROUNDED THEORY STEP BY STEP REVISITED, BEYOND PRACTICAL MANAGEMENT - Pongtiku, Arry; Leung, Big (Jurnal Aplikasi Manajemen, 2017)
A critical question is Was the theory which I developed really Grounded Theory (GT)?. GT aims to develop a new theory, it is perhaps one of the most abused phrases in a qualitative study. Increasingly, researchers are making claims to have used a GT approach. This method is a relatively little productive discussion in management literature. Grounded Theory of mode 2 knowledge production system brings together the supply side'of knowledge, including universities, with the ‘demand side', including business. The whole system depends for its effectiveness on a rapid interplay between management theory and practice. Mode 2 clearly focuses on management actions and describes the importance of involvement of participants and researcher through multidisciplinary approaches. This paper explains the history of GT, principles of GT, data analysis, an example in a building: Competitive Stakeholder Theory and finally working out the complexity of GT.